Influence of microstructure and crystallographic texture on hydrogen diffusion in IF-steel - Başkaya, Ümran; UZUN, Ramazan; DAVUT, Kemal; KILIÇ, Yasemin; GÜNDÜZ, Oğuz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The relation between microstructure, crystallographic texture, and hydrogen diffusion was studied on a IF-steel. The steel samples were deep drawn to a strain level of 10%, 20%, 30% and 40% and then the hydrogen diffusion coefficients were determined using the Helios II system. Light optical microscope (LOM), scanning electron microscope (SEM) and electron backscatter diffraction (EBSD) were used for microstructural characterization and crystallographic texture studies. The dependence of microstructural parameters was evaluated by Pearson correlation coefficient (PCC) values. These evaluations showed that local misorientations, crystallographic texture, and dislocation densityare interdependent. The PCC values show that grain size and dislocation density are the independent microstructure related parameters. These parameters were used to build a model to predict the hydrogen diffusion coefficient by multiple linear regression analysis. A sensitivity analysis was also performed with this model to understand to which parameter the hydrogen diffusion is most sensitive. The results of this analysis show that hydrogen diffusion is more sensitive to dislocation density, suggesting that dislocations are more effective trapping sites for hydrogen atoms. On the other hand, grain boundaries are less effective trapping sites since they also provide an additional diffusion mechanism.